Penerapan Manajemen Risiko Berbasis ISO 31000 pada Industri Fashion dan Aksesoris Fashion : Studi Kasus Brand Elcustom - Maliha Rizka Humaira; Fatimah Rahman; Alma Aulia Siffa; Susi Nurohimah; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the implementation of risk management based on the ISO 31000 framework in a micro, small, and medium enterprise (MSME) engaged in the fashion and accessories sector with 100% online sales operations. The business has been operating on e-commerce platforms such as Shopee, Tokopedia, TikTok, and Lazada for approximately five years and faces multiple risks including product defects, return rates due to consumers’ expectations, shipping delays in COD systems, fluctuations in raw material prices, increases in logistics costs, reduced margins, over-budgeting in production, depreciation of sewing machines, and human error within organizational operations. This research applies a qualitative descriptive approach through observation and interviews with business owners and operational workers. The results of the study show that the company has implemented risk identification and digital inventory monitoring but has not yet applied a structured risk assessment and treatment plan according to ISO 31000. Strengthening risk communication, key performance indicators (KPIs), and supplier contract management are recommended to enhance business sustainability.